5-Fluorouracil Neurotoxicity in the Absence of Dihydropyrimidine Dehydrogenase Deficiency Case Report. (April 2022) - Jules, Rebecca; Thaper, Arushi; Foster, Ryan; Ameli, Pouya; Robinson, Christopher; Pizzi, Michael; Babi, Marc-Alain; Maciel, Carolina B.; Busl, Katharina M.; Reddy, Raju; Roth, William
5 fluorouracil (5-FU)-related neurotoxicity is a rare and severe complication of 5-FU administration. Dihydropyrimidine dehydrogenase (DPD) deficiency is associated with an increased risk of serious adverse reactions due to its role in 5-FU metabolism. We report a case of acute reversible neurotoxicity with global areas of diffusion restriction in a patient with colorectal adenocarcinoma being treated with leucovorin calcium, 5-fluorouracil, and oxaliplatin (FOLFOX) without DPD deficiency following uridine triacetate administration.